The Effect of Maternal Fatty Acid Desaturase Single Nucleotide Polymorphism rs174602 and Prenatal Supplementation with Docosahexaenoic Acid on the Offspring Metabolome. (29th May 2020) - Tandon, Sonia; Gonzalez-Casanova, Ines; Barraza-Villarreal, Albino; Romieu, Isabelle; Demmelmair, Hans; Dommarco, Juan Rivera; Jones, Dean; Koletzko, Berthold; Stein, Aryeh; Ramakrishnan, Usha
Abstract: Objectives: To assess if maternal fatty acid desaturase ( FADS ) single nucleotide polymorphism (SNP) rs174602 modifies the effect of prenatal DHA supplementation on the offspring metabolome at age 3 months. Methods: Data were obtained from POSGRAD, a double-blind randomized controlled trial in Mexico in which 1094 women received 400 mg/day of algal DHA or a placebo (corn and soy oil) from mid-gestation until delivery. Genotyping was performed using maternal blood samples collected from women at baseline. Using liquid chromatography with high-resolution mass spectrometry, untargeted metabolomics was performed on plasma samples obtained from a random subsample of 112 offspring of POSGRAD participants at 3 months of age. Discriminatory metabolic features were selected via linear regression ( P < 0.05); false discovery rate (FDR) was controlled for using the Benjamini-Hochberg method (q = 0.2). Analyses were adjusted for infant sex. Effect modification by FADS SNP rs174602 was assessed using two-way analysis of variance. Pathway enrichment analysis was performed with Mummichog ( P < 0.05). Subgroup analyses were performed by rs174602, where the study population was grouped into carriers (TT, TC; n  = 70) and non-carriers (CC; n  = 42) of the minor allele. Results: We identified 279 metabolic features that differed significantly between infants whose mothers received prenatal DHA ( n  = 59) versus placebo ( n  = 53); however, zero features remained significant after FDR correction. In the DHA * SNP rs174602 interaction analysis, following FDR correction, 346 differentially expressed features were identified. In the subgroup analysis, positively enriched fatty acid metabolism and decreased amino acid and vitamin B3 metabolism pathways were seen among carriers in the DHA group compared to placebo, whereas differentially enriched TCA cycle and omega-6 fatty acid metabolism pathways were observed by treatment group among non-carriers. Conclusions: Maternal SNP rs174602 modified the effect of prenatal DHA supplementation on the infant metabolome at 3 months of age, particularly with regards to fatty acid metabolism. These findings provide additional support for the suggestion that differences in FADS genotype may explain inconsistent results observed across DHA supplementation trials. Funding Sources: NIH, Nutricia Foundation, Laney Graduate School, and Conacyt, Mexico.